The role of integrated reporting on global warming in achieving the requirements of international auditing standard 3410 an applied study in a sample of the local environment - Ali, Safa Ali Rasheed; Al-Basha, Adel Subhi (Edelweiss Applied Science and Technology, 2024)
The research aims to evaluate the role of assurance services according to Standard 3410 in enhancing the credibility of integrated reporting on global warming and its confirmation in local refineries (Dura and Shuaiba refineries) and to identify the challenges facing the application of assurance services through integrated reporting on global warming in order to propose solutions to overcome the challenges and activate the role of assurance services in enhancing the quality of integrated reporting on global warming and to analyze the level of application of Standard 3410 in assurance services through integrated reporting on global warming, where the importance of the research appears in terms of its role in bridging the knowledge gap and achieving practical benefits, as this research is distinguished by scientific importance A prominent work that deals with a modern professional issue that has not received sufficient attention in Iraq, despite the need for it by stakeholders, as the research focuses on criterion 3410, taking into consideration The associations with the standard 3000 are that it highlights the importance of assurance services in expanding the scope of services provided by auditors, which leads to increasing the importance and role of audit offices and enhancing their position in the market and increasing The value and benefit of the auditing profession relative to the users of financial reports, thus improving the quality of their decisions and increasing their confidence in the profession, as well as exploiting the skills and experience of accountants in The field of assurance services through reliance on integrated reporting of global warming and what contributes to addressing the problems facing its application. The research was based on a main hypothesis that "there is a statistical relationship with a significant level of moral significance between integrated reporting on global warming and achieving the requirements of Standard 3410." The researcher reached a set of conclusions, the most prominent of which is that the emergence of integrated reporting represents a qualitative addition to the services provided by the auditor, as its role has changed significantly from the traditional services associated with the statements. Financial and non-financial, and the auditor has become providing new services represented in his confirmation to ensure the information and its quality, which means that his role is no longer limited to verifying financial accuracy only, but also covers other aspects to ensure transparency and accuracy in the information provided, especially with regard to global warming. Based on these conclusions, the researcher has presented a number of recommendations, the most important of which is working on preparing a proposed framework for integrated reporting on global warming to be referred to when problems occur in scientific application, including a clear and comprehensive description of the theoretical concepts associated with all types of assurance services, especially with regard to integrated reporting on global warming according to International Auditing Standard 3410 Keywords: Integrated reporting, global warming, International Auditing Standard 3410, local environment.